The China-Czech Partnership in Global Trade - Zhu, Yanghao; Štěrbová, Ludmila, 1957-; Šaroch, Stanislav, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the developing economic and investment ties between China and the Czech Republic in terms of the "Belt and Road Initiative" (BRI) and the "16+1 Cooperation Mechanism". Since officially creating the strategic partnership between China and the Czech Republic in 2016, bilateral trade has grown considerably, but vulnerabilities in terms of structural imbalances and weak inflows of foreign direct investment (FDI) have continued. This thesis also seeks to examine these developments by considering the strategic objectives in China's foreign economic agenda in Central Europe and the Czech Republic, as well as Czech Republic responses in terms of the European Union more widely. Thesis applies a mixed-method approach by using quantitative trade and investment data in conjunction with policy documents, academic materials, and textual interpretations derived from media reports, and also examines the role of global shocks (e.g., the Sino-US trade war, COVID-19 pandemic, and Ukraine crisis) on the bilateral relationship. This thesis further pinpoints areas for future cooperation that could include advanced manufacturing, digital innovation, and green energy.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses